Effectiveness and safety of warm needle acupuncture on children with cerebral palsy: Protocol for a systematic review and meta-analysis. Issue 13 (March 2019) - Chen, Long An; Liu, Hui Tuan; Huang, Cihui; Zhang, Lu; Zeng, Fangdong; Xie, Bo
Abstract: Background: Warm needle acupuncture (WNA) is an integral part of the acupuncture therapy, which combines acupuncture and moxibustion. Children with cerebral palsy (CP) is a common disease in children, which seriously affects children's growing development, physical and mental health. The clinical practice indicates that WNA has a therapeutic effect on children with CP. Here we will provide a protocol to explore the effectiveness and safety of WNA for children with CP. Methods: We will search the randomized controlled trails (RCT) literatures of WNA for children with CP in 5 English databases [PubMed, Web of Science, EMBASE, the Cochrane Central Register of Controlled Trials (Cochrane Library), and WHO International Clinical Trials Registry Platform (ICTRP)] and 4 Chinese databases [Chinese National Knowledge Infrastructure (CNKI), Chinese VIP Information, Wanfang Database, and Chinese Biomedical Literature Database (CBM)]. Activity of Daily Living Scales (ADL) of the patient will be considered as the primary outcome and the secondary outcome will include 88 items of gross motor function scale (GMFM-88), Gesell Growth Table (GGT), Criteria for judging efficacy and adverse events caused by WNA such as dizziness, nausea, vomiting, weariness, etc. The selection of the studies will be performed by EndnoteX7 software. And we will conduct all analyses with RevMan software V5.3. Result: This study will provide a rational synthesis of current evidences for WNA on children with CP. Conclusion: The conclusion of this study will provide evidence to judge the effectiveness and safety of WNA on children with CP. Registration: PROS-PERO CRD42019122034